2007
DOI: 10.1590/s1020-49892007000800007
|View full text |Cite
|
Sign up to set email alerts
|

Community-directed risk assessment of mercury exposure from gold mining in Suriname

Abstract: This project showed that a democratic approach to science does not automatically compromise the orderly search for answers. Specifically, our experience in Kwakoegron suggests that the collaborative relationship that emerges by empowering an indigenous community to initiate its own research projects, and address the needs it identifies, can contribute positively to the risk assessment process. This project showed that when Kwakoegron was acknowledged as an equal partner, the risk assessment process led to an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
18
0
3
Order By: Relevance
“…This detailed article summarized the results from 26 studies, showing that the exposure to inorganic Hg vapor is high, and that toxic effects have to be considered. Some relevant papers in different countries with ASGM showed that Hg levels in any analyzed biomarker were higher compared to control groups or reference values, and in some studies clinical symptoms or negative results for subclinical parameters were identified [7,8,13,14,26,28,29,31,32,[53][54][55][56][57][58][59][60]. These results are very similar to our results.…”
Section: Literaturesupporting
confidence: 90%
“…This detailed article summarized the results from 26 studies, showing that the exposure to inorganic Hg vapor is high, and that toxic effects have to be considered. Some relevant papers in different countries with ASGM showed that Hg levels in any analyzed biomarker were higher compared to control groups or reference values, and in some studies clinical symptoms or negative results for subclinical parameters were identified [7,8,13,14,26,28,29,31,32,[53][54][55][56][57][58][59][60]. These results are very similar to our results.…”
Section: Literaturesupporting
confidence: 90%
“…However, few studies have been published. Recent studies have shown high levels of Hg in people from interior communities on the Saramacca River [12]. Hg vapor from gold shops in the capital also contributes to exposure of people in their vicinity even if it is difficult to assess [13].…”
Section: Introductionmentioning
confidence: 99%
“…Communities are aware of their exposure to Hg, its link to gold mining, and the potential for neurological toxicity. However, the majority of individuals remain poorly informed about the precise causes, symptoms, and possible remedies [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Human health risks due to mercury exposure are well known with kidney damage and signs of highly devastating neurotoxicity particularly in the central and peripheral nervous systems (Aschner and Aschner 1990;Langford and Ferner 1999;Magos 1997;Tchounwou et al 2003;Zalups 2000) as prime examples. DiVerent studies (Bose-O'Reilly et al 2008;Castilhos et al 2006;Corbett et al 2007;Cortes-Maramba et al 2006;da Costa et al 2008;Peplow and Augustine 2007;van Straaten 2000a, b;Veiga et al 2006) show that mercury contamination is still an active worldwide issue for both humans and the environment.…”
Section: Introductionmentioning
confidence: 99%